The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1080/15299730802073676
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualization and Treatment of Psychogenic Non-Epileptic Seizures

Abstract: Psychogenic non-epileptic seizures (PNES) frequently present co-morbidly with a range of somatic and psychiatric conditions. This review discusses the relationship between PNES, a number of co-morbid psychiatric symptoms, early attachment trauma, and disruption of neurological development. We suggest that it may be clinically useful to understand PNES with reference to three patterns of co-morbidity and trauma history. In the first group, PNES are one symptom of a response to severe, chronic trauma and invalid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…It is also important to investigate the characteristics and the circumstances of the traumatic event in patients with PNES in order to determine the best type of psychotherapy [51]. Currently, there are no guidelines regarding treatment of PNES because the symptoms reflect a variety of different defense mechanisms which can give rise to the symptoms [12].…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to investigate the characteristics and the circumstances of the traumatic event in patients with PNES in order to determine the best type of psychotherapy [51]. Currently, there are no guidelines regarding treatment of PNES because the symptoms reflect a variety of different defense mechanisms which can give rise to the symptoms [12].…”
Section: Discussionmentioning
confidence: 99%
“…PNES constitute a heterogeneous population with varying degrees of psychiatric background and somatic complaints. 22,23 It is unlikely that one single model can explain PNES for all subgroups of patients. Certain traits that describe cognitive and emotion processing styles have been identified in PNES.…”
Section: A Conceptualization Model For Pnesmentioning
confidence: 99%
“…A previous study by our team 21 compared FDS patients according to trauma history and found that those who reported a history of trauma had significantly more psychiatric comorbidities and stronger dissociative tendencies. Likewise, Quinn et al 43 divided patients with FDS into three groups according to their trauma experience backgrounds and psychiatric comorbidities on the basis of a literature review. In their first group, the seizures appeared to be a response to severe and chronic trauma.…”
Section: Discussionmentioning
confidence: 99%